Nanoceria decorated flower-like molybdenum sulphide nanoflakes: an efficient nanozyme for tumour selective ROS generation and photo thermal therapy. Issue 55 (21st June 2019) - Murugan, Chandran; Murugan, Nagaraj; Sundramoorthy, Ashok K.; Sundaramurthy, Anandhakumar
Abstract : Nanoceria decorated flower-like MoS2 nanoflakes as a nanozyme for cancer photothermal therapy. Abstract : We report nanoceria (NCeO2 ) decorated flower-like MoS2 nanoflakes as a nanozyme for cancer photothermal therapy (PTT). They exhibited enzyme-like activity for selectively killing tumor cells by ROS induction. The NCeO2 decoration significantly improved the photoconversion efficiencies (PCEs) of MoS2 nanoflakes when a NCeO2 concentration of ≤0.5 mg mL −1 was used for synthesis. The novel material demonstrated here showed high photostability and PCE, without any systemic toxicity for cancer PTT.